Justice and the politics of capabilities Sen, Nussbaum and Navarro - Cvijanović, Hrvoje (2019)
Linking the idea of justice with human dignity through the 'politics of capabilities' is a recent theoretical project advanced by Amartya Sen and Martha Nussbaum and inspired by the shortcomings of Rawls's understanding of justice. Rawls's view on the redistribution of resources or primary goods has nothing to say about someone's capabilities to use these goods, so the idea of capabilities becomes central since it is focused on the way of life a person has a reason to value. The article discusses Sen and Nussbaum's development of the capabilities approach and their criticism of Rawls's fundamental premises about justice. Although the capabilities approach attempts to rectify injustices that Rawls failed to address properly, there are limitations of that approach as well. At the end, it is shown that capabilities are valued in relation to their contribution to the system of production – having more capabilities enhances someone's socio-economic position within the given structure – but this does not question the existing power relations and the very structure that perpetuate inequalities. Hence, the author agrees with the line of criticism that invokes the issue of power relations provided by Vicente Navarro, yet extending this criticism to Rawls's theory of justice for not fundamentally questioning the power relations inherent in the institutions reproducing social injustices.
Povezivanje ideje pravednosti s ljudskim dostojanstvom kroz "politike sposobnosti" recentan je teorijski projekt koji uvode Amartya Sen i Martha Nussbaum, inspirirani nedostacima Rawlsova razumijevanja pravednosti. Naglašava se da Rawlsovo stajalište o preraspodjeli resursa ili primarnih dobara ne uzima u obzir sposobnosti pojedinaca da koriste ta dobra pa upravo stoga pojam sposobnosti postaje ključnom idejom koja predstavlja način života koji netko ima razloga cijeniti. Autor razmatra razvoj pristupa sposobnostima i kritiku Rawlsovih temeljnih pretpostavki o pravednosti u radovima Sena i Nussbaum. Iako pristup sposobnostima pokušava ispraviti nepravde vezane za ljudsko dostojanstvo koje Rawls nije uspio riješiti, postoje ozbiljna ograničenja tog pristupa. Naposljetku je pokazano da se sposobnosti vrednuju prema njihovu doprinosu sustavu proizvodnje – ako netko ima više sposobnosti, to povećava njegov društveno-ekonomski položaj unutar zadane strukture – ali ne propituju se postojeći odnosi moći i struktura koja održava nejednakosti. Stoga je autor suglasan s kritikom pristupa sposobnostima Vincenta Navarra, ali i proširenju kritike na Rawlsovu teoriju pravednosti, zato što ne dovodi u pitanje temeljne odnose moći koji su inherentni institucijama i njihovoj reprodukciji društvenih nepravdi.
Bibliografske bilješke uz tekst ; bibliografija: str. 177-178.
Summary ; Sažetak.
Keywords: Pravda -- Sposobnosti; Sen, Amartya -- Nussbaum, Martha -- Rawls, John -- Navarro, Vincent